Self-concept in preadolescence: A brief version of AF5 scale - Pau García-Grau; Daniel Ayora Pérez; Ferran Calabuig Moreno; Vicente Javier Prado-Gascó (Universidade Estadual Paulista (UNESP), 2014)
The purpose of this study was to analyze the psychometric properties of a brief version of the AF5 questionnaire (García & Musitu, 2001) using exploratory and confirmatory techniques on a preadolescent population in the Valencian community (Spain). The sample was made up of 541 participants between 10 and 12 years old, 55.1% (298) boys and 44.9% (243) girls. After observing the results of different reliability and validity analyses (exploratory factor analysis (EFA) and confirmatory factor analysis (CFA)), it was found that the reduced scale consisting of 20 items showed a similar reliability and validity to the original scale. The factorial structure also fits that of the original model established a priori. According to the results of the study, the use of this diagnostic tool with Spanish children seems justified.